The Effect of (Aquafina) Drinking Water on the Corrosion Rate and Hardness of (Al-Si) and (Al-Mg-Si) Alloys - Almtori, Safaa A. S. (Basrah Journal for Engineering Sciences, 2007)
The present work investigates the effects of drinking water on the erosion- corrosion rate and Vickers hardness of (Al-Si) and (Al-Mg-Si). (Al-Si) alloy Which is well-known as casting alloy with high wear resistance, low thermal expansion coefficient, good corrosion resistance and improved hardness at a wide range of temperatures While (Al-Mg-Si) alloys have good formability, weld ability, machine ability and corrosion resistance. The alloys specimens which are used for piping and containing water and carbonated water were exposed in erosion- corrosion system in factories by using drinking water type AQUAFINA as exposure media for different exposure time (1-30)h. to measure the erosion-corrosion rate. The results show that there is small different in the rate of corrosion, moreover (Al-Mg-Si) alloy have high resistance to erosion-corrosion in drinking water due to the consisting of (Mg2Si) phase which is precipitate as fine particles due to resist dislocations movement lead to high corrosion strength and the (Al-Si) alloy have high Vickers hardness at natural aging due to the present of high ratio hardening silicon element.